2022
DOI: 10.3390/sym14112382
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Vibrational Parameters of a D∞h-Symmetric Triatomic Molecule in a Laser Plasma

Abstract: We estimate theoretically the strong-field-modified vibrational parameters of three-atomic ABA molecules with D∞h symmetry in a laser-induced plasma. The linear CO2 and CS2 molecules in the X1Σg state are considered as examples. We show that double degeneracy of the Πu mode is removed due to reduction of the ABA molecule symmetry by the laser field. The linear form of ABA molecule is preserved, the bond length being elongated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In ref. [14], it is shown that the relative change of the C-O bond length amounts to 0.43%, and that of the Ω y frequency is −1.0%, at the laser field intensity of 1.00 × 10 14 W/cm 2 .…”
Section: Modification Of the Vibrational Parameters Of Co 2 In A Lase...mentioning
confidence: 92%
See 4 more Smart Citations
“…In ref. [14], it is shown that the relative change of the C-O bond length amounts to 0.43%, and that of the Ω y frequency is −1.0%, at the laser field intensity of 1.00 × 10 14 W/cm 2 .…”
Section: Modification Of the Vibrational Parameters Of Co 2 In A Lase...mentioning
confidence: 92%
“…The change in the vibrational parameters of the CO 2 molecule in the laser field (2) has been recently investigated in detail in ref. [14]. In the lowest order, this change is linear in the radiation intensity.…”
Section: Modification Of the Vibrational Parameters Of Co 2 In A Lase...mentioning
confidence: 94%
See 3 more Smart Citations